Book review: Fulcher, L, and Moran, A. (2003). Sisters of pain: An ethnography of young women living in secure care. Cape Town: CYC-Net Press, 262 pp., ISBN 978-1- 928212-01-0 - Carole Dearie (Scottish Journal of Residential Child Care)
The title, Sisters of Pain, invites the reader from the onset to be aware that the content of this book will not be a good choice for bedtime or holiday reading. Leon Fulcher and Aliese Moran take us on a journey into the lives of young women who spent time within a secure facility in the USA, and the voices of the girls who share their stories is without doubt powerful and thought provoking. I approached reading this book through the lens of a practitioner/manager within a secure facility, but I was only too aware that a professional perspective was not to be in isolation of a personal one and this will be reflected in the review.